Enduring Methods – Editors' Introduction. (June 2020) - Jansen, Jan; Doortmont, Michel R.; Hanson, John H.; van den Bersselaar, Dmitri
Abstract : The 2020 volume of History in Africa is the eleventh produced by the current editorial team. It will also be the last, as we are handing over to a brand-new team, consisting of esteemed colleagues Lorelle Semley, Sandra Barnes, Bayo Holsey, and Egodi Uchendu.